Uncertainty in a Medico’s Mind: The Way Out - Surajit Bhattacharya; Kaushik Bhattacharya; Neeta Bhattacharya; Subham Sarthak; Divya Sudarshan (National Board of Examinations Journal of Medical Sciences)
The transition from medical education to clinical practice is often marked by significant uncertainty for new medical graduates. This uncertainty stems from a variety of factors, including the complexity of real-world patient care, the application of theoretical knowledge to practical scenarios, and the emotional and psychological weight of clinical decision-making. New medicos are thrust into environments where they must navigate intricate medical conditions, make decisions under time pressure, and manage expectations from patients, families, and healthcare teams. Despite rigorous training, the gap between theoretical knowledge and clinical application can foster self-doubt and feelings of inadequacy.